Dialogan sobre las diferentes costumbres que existen en sus familias al celebrar la navidad - Bocanegra Agreda, Yliana Enriqueta (2019)
This learning session has the title: "Share the cultural manifestations, traditions and _x000D_ customs of your family that make you feel proud of its origin"; which is designed to be _x000D_ developed with 4 year old students of the initial level. _x000D_ The introduction is intended for class planning, performance to be evaluated, _x000D_ evidence of learning and the assessment instrument to be used. Likewise, to the didactic _x000D_ sequence that is applied in the area of Social Personnel, which allows children to develop _x000D_ competence as a know how to combine skills, through investigative activities based on _x000D_ curiosity, observation and questioning that they do when interact with the physical world, so _x000D_ they exchange ways of thinking through dialogue and contrast it with the hypotheses to build _x000D_ new knowledge based on their purposes. _x000D_ In the second chapter, the theoretical framework is exposed, supporting the raffled _x000D_ capacity, for which the bibliographic inquiry was made, taking as reference those authors _x000D_ who describe the concepts on cultural manifestations, traditions and customs. _x000D_ In the third chapter, it is dedicated to pedagogical support, referring to _x000D_ psychopedagogical principles, pedagogical processes, didactic processes of the area, _x000D_ medium and material techniques in the methodological process, as well as evaluation _x000D_ procedures and instruments.